2022
DOI: 10.1007/s10389-021-01663-2
|View full text |Cite
|
Sign up to set email alerts
|

Methods of engagement and levels of involvement of stakeholders in the management of work-related musculoskeletal disorders: A systematic scoping review

Abstract: Aim: Stakeholders have an important role in both prevention and management of work related musculoskeletal disorders (WRMSDs). However, the scope of practice is unclear regarding the methods and levels of stakeholder engagement (SE) in management of WRMSDs. The aim of this review is to map the literature regarding various methods and levels of SE and how it is best implemented when managing WRMSDs. Methods: A systematic literature search was conducted in several major databases using key search phrases. Variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 65 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…It was also reported that the PE process could trigger health difficulties, generate self-stigma and hinder a meaningful cocreation process 26 30 45 49 50 56. A recent scoping review concludes that all stakeholders should take on a more progressive role to convert from a pro-forma PE approach to meaningful levels of cocreation 6. A meaningful level of engagement embraces empowerment to participate with equity as a core value 38 44 69…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also reported that the PE process could trigger health difficulties, generate self-stigma and hinder a meaningful cocreation process 26 30 45 49 50 56. A recent scoping review concludes that all stakeholders should take on a more progressive role to convert from a pro-forma PE approach to meaningful levels of cocreation 6. A meaningful level of engagement embraces empowerment to participate with equity as a core value 38 44 69…”
Section: Discussionmentioning
confidence: 99%
“…26 30 45 49 50 56 A recent scoping review concludes that all stakeholders should take on a more progressive role to convert from a proforma PE approach to meaningful levels of cocreation. 6 A meaningful level of engagement embraces empowerment to participate with equity as a core value. 38 44 69 Outcome Even if our findings indicate that patient representatives engaged in the cocreation process may contribute to improved care, there is a lack of research reporting this as hard outcomes.…”
Section: Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also excluded any PSW who sought medical help and were under any pain medication at the time. As the SMART Drive research group encourages the local stakeholders and participants to establish equal partnership and engagement in musculoskeletal research and service development (Fearnley et al 2022), the final study report and summary of study findings were agreed to be shared with the PSW managers, work supervisors and participants who would be the end users of the study. The participants at the study plant did not rotate jobs and all the data was collected on time during the working hours of a current job.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…The study findings would help the researchers to work with the PSW community and industry to form a team of equal partnership, engagement and involvement of the PSW workforce in the development of an appropriate intervention. It is recommended that any musculoskeletal health and wellness programs should incorporate a partnership approach engaging PSW as equal workers (Fearnley et al 2022), so that the specific needs and expectation of the PSW can be captured in the design and implementation of any musculoskeletal health wellness programs.…”
Section: Practice and Industry Implicationsmentioning
confidence: 99%